Economic Feasibility and Decarbonization Incentives of Sugarcane Biogas Production Pathways - Flavio Eduardo Fava; Lucílio Rogério Aparecido Alves; Thiago Libório Romanelli (Agriculture)
Challenges in investment decisions for new fuels remain due to uncertain scenarios regarding profitability. There is also a challenge to improve production efficiency and waste utilization, either for biomass or by-products. This study evaluates the economic potential of biomethane production within sugarcane biorefineries through the principles of the circular economy and economic feasibility. To obtain price data for CBios, Brent crude oil, and natural gas, stochastic models based on GBM and Monte Carlo simulations were applied to project prices and assess revenue potential over a 10-year horizon. Price data were incorporated to assess market correlations and revenue scenarios. Key findings reveal that biomethane’s price stability, driven by its strong correlation with oil markets, supports its viability as a renewable energy source, while CBio presents a weak correlation and limited price predictability with present challenges for long-term planning. Economic modeling indicates high investment returns, with IRR values surpassing 35% in conservative scenarios and payback periods from 2 to 6 years. These results highlight biomethane’s potential for energy efficiency, carbon emission reduction, and the creation of new revenue through waste use. We conclude that targeted investments in biomethane infrastructure, coupled with policy and market support, are essential for achieving global sustainability goals.